2021
DOI: 10.3390/ijerph18116014
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Potentially Toxic Elements (PTEs) in Urban Soils from Salzburg, Thessaloniki and Belgrade: An Insight into Source Identification and Human Health Risk Assessment

Abstract: Concentrations of potentially toxic elements (PTEs) (Al, As, Cd, Cr, Cu, Ni, Pb, and Zn) were measured in topsoil samples collected from parks in the cities of Salzburg (Austria), Thessaloniki (Greece), and Belgrade (Serbia) in order to assess the distribution of PTEs in the urban environment, discriminate natural (lithogenic) and anthropogenic contributions, identify possible sources of pollution, and compare levels of pollution between the cities. An assessment of the health risks caused by exposure to PTEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 72 publications
2
10
1
Order By: Relevance
“…A comparison of PTE content in urban soils in some Serbian cities and European urban soils is shown in Table 3. When comparing results of PTEs content obtained in this research with results from our previous research [4,73], levels of Mn were found to be similar, but Cr, Cu, Ni, Pb, and Zn concentrations were higher. On the other hand, Cr, Cu, Pb, and Zn content in soils in Novi Sad [74], Lisbon [79], and Thessaloniki [73] was similar, but Ni was somewhat lower than the levels measured in this research (Table 2).…”
Section: Pseudo-total Content Of Selected Ptes In Examined Urban Soilssupporting
confidence: 67%
See 1 more Smart Citation
“…A comparison of PTE content in urban soils in some Serbian cities and European urban soils is shown in Table 3. When comparing results of PTEs content obtained in this research with results from our previous research [4,73], levels of Mn were found to be similar, but Cr, Cu, Ni, Pb, and Zn concentrations were higher. On the other hand, Cr, Cu, Pb, and Zn content in soils in Novi Sad [74], Lisbon [79], and Thessaloniki [73] was similar, but Ni was somewhat lower than the levels measured in this research (Table 2).…”
Section: Pseudo-total Content Of Selected Ptes In Examined Urban Soilssupporting
confidence: 67%
“…When comparing results of PTEs content obtained in this research with results from our previous research [4,73], levels of Mn were found to be similar, but Cr, Cu, Ni, Pb, and Zn concentrations were higher. On the other hand, Cr, Cu, Pb, and Zn content in soils in Novi Sad [74], Lisbon [79], and Thessaloniki [73] was similar, but Ni was somewhat lower than the levels measured in this research (Table 2). Similarities in terms of PTE content were also found in soils from Šabac [75] and Kragujevac [76], where concentrations of most of the examined elements were similar to those determined in this research, with the exception of the higher content of Cr in Kragujevac and Mn in Šabac.…”
Section: Pseudo-total Content Of Selected Ptes In Examined Urban Soilssupporting
confidence: 67%
“…PTEs in the environment originate from various human activities (mining, chemical, and metallurgical industries, smelting procedures, agriculture, traffic, etc.) and natural (lithogenic) sources such as volcanic eruptions and weathering of element-containing rocks. , Mining activities involving many processing methods such as grinding the rock and ores, recovering the desired fraction, and dumping the waste into a tailing or holding pond are among the main sources of PTEs in the environment. PTE elements released into the surrounding environment during mining not only affect soil quality but also threaten food safety of crops grown in polluted soil and human health. In addition, exposure to PTEs can pose a health problem for miners. , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, analysis of urban soils is important since the chemical composition of soil reflects both the soil lithogenic and the anthropogenic inputs of pollutants from industrial facilities and traffic. So far, most research has focused on the influence of the labile fraction of heavy metals in soil on bioavailability [8,17,[21][22][23], with only a small number of studies discussing the effects of the fractionation of PTEs in soils (especially acid-soluble, oxide-bound, organic matter-bound fractions) as a factor of the bioaccumulation of elements by plants in urban sites. It is recognized that the labile fraction determined by sequential extraction can enter plants easily; thus, the ecological effect of potentially toxic elements is closely related to mobility and speciation of these chemical elements [8,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%